Pengembangan Konten Website tentang Informasi Karier Berbasis 4C’s Bagi Siswa SMKN 2 Malang - Yusrolana Nurilah; Muslihati Muslihati; Triyono Triyono (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2021)
Abstract: The research was intended to produce a website content about career information for students of SMKN 2 Malang. This creative and innovative website content is student-centered. Today’s millennial generation also need to develop 4C’s skills in everyday life to prepare for education and employment in the 21st century. Development research adapted into the five steps of Borg and Gall (1983). Trials consist of an initial product trials and limited field trials. An initial product trials were conducted by BK material experts and media experts, while limited field trials were carried out by counselors. The instrument was validated using logical validity based on the aspects of accuracy, usefulness, convenience and attractiveness. Quantitative data were analyzed using an inter-rater agreement, while qualitative data were analyzed using the Miles and Huberman model input from experts and potential product users. The results of the assessment show that website content products have a very high acceptance so that they are suitable for use in BK services regarding 4C’s based career information for vocational students. It is hoped that the counselor can provide this information service to students by understanding the infographic as a guide to using the website and adjusting it to the activity procedures on the RPL-BK. For future researchers, it is hoped that they can test the effectiveness of the product in order to obtain more accurate results. In addition, it can also combine with new models or theories to make it more complete and interesting. Abstrak: Penelitian ini bertujuan untuk menghasilkan konten website tentang informasi karier siswa SMKN 2 Malang. Konten website secara kreatif dan inovatif ini berpusat pada siswa. Generasi millenial zaman sekarang juga perlu mengembangkan keterampilan 4C’s pada kehidupan sehari-hari demi mempersiapkan pendidikan dan pekerjan di abad ke-21. Penelitian pengembangan mengadaptasi menjadi lima langkah Borg and Gall (1983). Uji coba terdiri dari uji coba produk awal dan uji lapangan terbatas. Uji coba produk awal oleh ahli materi BK dan ahli media, sedangkan uji lapangan terbatas dilakukan oleh konselor. Instrumen divalidasi dengan menggunakan validitas logika berdasarkan aspek ketepatan, kegunaan, kemudahan dan kemenarikan. Data kuantitatif dianalisis menggunakan inter-rater agreement, sedangkan data kualitatif dianalisis menggunakan model Miles dan Huberman dari masukan para ahli dan calon pengguna produk. Hasil penilaian menunjukkan bahwa produk konten website memiliki keberterimaan yang sangat tinggi sehingga layak digunakan pada layanan BK tentang informasi karier berbasis 4C’s bagi siswa SMK. Diharapkan kepada konselor dapat memberikan layanan informasi ini kepada siswa dengan memahami infografis sebagai petunjuk penggunaan website dan disesuaikan pada prosedur kegiatan dalam RPL-BK. Bagi peneliti selanjutnya, diharapkan dapat menguji keefektifan produk guna memperoleh hasil yang lebih akurat. Selain itu, dapat juga dengan mengkombinasikan dengan model atau teori baru agar lebih lengkap dan menarik.